Pengabdian Kepada Masyarakat Guru Pengelola Koperasi di SMKN Jakarta Pusat - Nurmalasari, Dewi; Marsofiyati, Marsofiyati; Swaramarinda, Darma Rika; Puruwita, Dita (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
Through the results of observations and in-depth interviews, it is evident that most teachers (85%) who are school cooperative managers have never had the opportunity to attend training/workshops on the management of school cooperatives that are good and right. Most teachers who become school cooperative managers (90%) do not have an economic / accounting education background. Most school cooperatives in public vocational high schools majoring in technology and engineering are not legal entities. The solutions offered are training and mentoring as well as improving the legal status of school cooperatives to become cooperative legal entities. The method or approach offered to solve partner problems is training, mentoring, and supervision. At the time of the training, we provided material regarding Recognize Self Potency and also provided the SIKOP software and the guidebook.